(untitled) (PRÁXIS EM SAÚDE, 2025)
This study addresses the relevance of family participation in the psychotherapy of children with Autism Spectrum Disorder (ASD), through a literature review conducted using open-access databases such as Scielo, LILACS, PubMed, Cochrane Library, and APA. The aim of the research was to understand the impact of the active presence of family members in the child’s therapeutic process. Five studies were selected out of 66 initially found, based on eligibility criteria. The qualitative analysis showed that parental involvement positively influences the child’s neurodevelopment and helps caregivers cope with stress and other emotional challenges. Although one of the studies presented inconclusive results, this was attributed to the scarcity of specific research on the topic rather than the ineffectiveness of family intervention. The review highlights that parental involvement is essential for the effectiveness of therapeutic approaches, promoting better outcomes in child development. The active presence of the family, combined with multidisciplinary support, significantly contributes to more effective and humanized care.